THE EFFECTIVENESS OF STARFRUIT (AVERRHOA BLIMBI L.) EXTRACT IN INHIBITING STAPHYLOCOCCUS AUREUS BACTERIA - Wulandari, Ayu (Postgraduate Program , Poltekkes Kemenkes Semarang, 2025)
Abstract:Â Strafruit (Averrhoa bilimbi L.) can be used to treat canker sores, stomach pain, mumps, rheumatism, coughs, bleeding gums, toothaches, healthy digestive function, removing stains on fabrics, overcoming fishy odors, being a cosmetic ingredient and improving the shine of goods. - Items made of brass. Belimbing wuluh contains active substances including flavonoids, tannins, and saponins which have antibacterial properties. Staphylococcus aureus is a commensal bacteria that can turn into a pathogen if there is a decrease in the body's immunity which can lead to systemic infection and bacteremia of the oral mucosa. Staphylococcus aureus infection is characterized by necrosis, inflammation and abscesses. Methods: In this study, the Literature Study method was used. Results: Starfruit (Averrhoa blimbi L.) is one of the many types of plants that are often used as traditional medicine. Staphylococcus aureus are bacteria that initially commensal can turn into pathogens if there is a decrease in body immunity which can lead to systemic infections and bacteremia of the oral mucosa. Staphylococcus aureus infection is characterized by necrosis, inflammation and abscesses. Conclusion: Based on the results of a search of several literatures that have been carried out by the author, it can be concluded that the extract of the star fruit (Averrhoa blimbi L.) has an inhibitory effect on the bacterium Staphylococcus aureus. In addition, the antibacterial content of star fruit (Averrhoa blimbi L.) such as flavonoids, tannins, and saponins can inhibit staphylococcus aureus bacteria.